2020
DOI: 10.3390/ijms21082759
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Successful Implementation of the Immune Checkpoint Inhibitors for Treatment of Glioblastoma

Abstract: Glioblastoma (GBM) is the most common and aggressive malignant glioma, treatment of which has not improved significantly in many years. This is due to the unique challenges that GBM tumors present when designing and implementing therapies. Recently, immunotherapy in the form of immune checkpoint inhibition (ICI) has revolutionized the treatment of various malignancies. The application of immune checkpoint inhibition in GBM treatment has shown promising preclinical results. Unfortunately, this has met with litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 86 publications
(180 reference statements)
0
45
0
6
Order By: Relevance
“…Immune checkpoint inhibitors, such as nivolumab, ipilimumab and pembrolizumab, have strikingly improved patient survival in solid tumors, such as non-small lung cancer and melanoma. However, the trials assessing the efficacy of immune checkpoint inhibitors in GBM are still disappointing ( 7 ). A retrospective study of the use of pembrolizumab in the treatment of recurrent CNS tumors, including GBM, demonstrated that patients treated with Pembrolizumab did not have improved survival ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immune checkpoint inhibitors, such as nivolumab, ipilimumab and pembrolizumab, have strikingly improved patient survival in solid tumors, such as non-small lung cancer and melanoma. However, the trials assessing the efficacy of immune checkpoint inhibitors in GBM are still disappointing ( 7 ). A retrospective study of the use of pembrolizumab in the treatment of recurrent CNS tumors, including GBM, demonstrated that patients treated with Pembrolizumab did not have improved survival ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the trials assessing the efficacy of immune checkpoint inhibitors in GBM are still disappointing ( 7 ). A retrospective study of the use of pembrolizumab in the treatment of recurrent CNS tumors, including GBM, demonstrated that patients treated with Pembrolizumab did not have improved survival ( 7 ). Another Phase III randomized trial comparing radiation and concomitant temozolomide with or without nivolumab showed that no progression-free survival benefits were obtained by the addition of nivolumab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sobretudo, enfrentar mitos e apresentar as neurociências básicas num panorama aplicado têm se demonstrado atalhos úteis entre a facilitação do aprendizado e a aproximação entre o paciente neurológico e os novos médicos, que poderão vislumbrar as imensas possibilidades de escolher esta especialidade escassa, interessante e com remuneração bastante recompensadora. D Diagnóstico 4,5,6,14,15,18,21,30,33,34,35,36,37,40,41,42,43,44,45,46,50,59,63,65,67,69,70,93,94,105,107,108,109,110,112,116,146,148,151,157,160,162,163,164,165,166,168,169,170,171,172,173,…”
Section: Conclusãounclassified
“…Possui uma alta sensibilidade e especificidade diagnóstica, sendo uma boa opção para locais sem recursos laboratoriais, onde está concentrada a maior incidência de casos da doença (TUCKER et al, 2013;Ho, E. L et al, 2015 de 19,5% (IC 95%: 10,5%), VPN 100% (IC 95%: 91,0% -100%) e uma razão de verossimilhança de 2,0 (p=0,0034), além de demais cálculos de acurácia diagnóstica, conforme Tabela 1. Sensibilidade (IC 95%) 88,9% (56,5 -99,4) 88,9% (56,5 -99,4) 100% 70,1 -99,5100% 70,1 -99,5Especificidade (IC 95%) 100% 95,2 -10089,6% (80,8 -94,6) 80,5% (70,3 -87,8) 50,6% (41,0 -62,6) P valor <0,0001 <0,0001 <0,0001 0,0034 VPP 100% (67,6 -100) 50,0% (28,0 -72,0) 37,5% (21,1 -57,3) 19,5% (10,4 -32,5) VPN 98,7% (93, 1 -99,9) 98,6% (92,4 -99,9) 100% (94 The results showed that patients with high viral load and low BMI had higher PLH incidence, and these data were statistically significant (p <0.05). Therefore, we conclude that the high viral load and low BMI in these patients can be considered risk factors for the development of CPL,however more studies should be performed.…”
Section: Introductionunclassified